Effects of berberine on the pharmacokinetics of florfenicol and levels of cytochrome P450 3A37, multidrug resistance 1, and chicken xenobiotic‐sensing orphan nuclear receptor mRNA expression in broilers. Issue 2 (11th November 2021) - Li, Sicong; Wang, Bin; Zhang, Min; Yuan, Dingsheng; Li, Jinliang; Li, Xuting; Liang, Ge
Abstract: Background: Berberine (BBR) is always used in combination with florfenicol for treating avian in China. Objective: This study aims to investigate the effects of BBR on the pharmacokinetics of florfenicol in broilers. Methods: Male broilers were randomly divided into the control group and the BBR group (BG). Note that 50 mg/kg BBR or sterile water was orally administrated to broilers. On the 8th day, florfenicol [30 mg/kg body weight (BW)] was orally administered to broilers in both groups. The plasma concentrations of florfenicol were determined by ultra‐high‐performance liquid chromatography (UHPLC). The levels of cytochrome P450 (CYP) 3A37, multidrug resistance 1 (MDR1), and chicken xenobiotic‐sensing orphan nuclear receptor (CXR) mRNA expression in the liver and jejunum were determined by the real‐time PCR. Results: The results showed that the Cmax, t1/2z, MRT(0‐∞), and AUC(0‐∞) of florfenicol in BG were significantly increased (by 55.71%, 28.32%, 35.19%, and 55.62%, respectively), while the Tmax and CLz/F of florfenicol were significantly decreased (by 52.13% and 35.82%, respectively). In BG, the levels of CYP3A37, MDR1, and CXR mRNA expression in the liver were significantly decreased to 0.72‐fold, 0.67‐fold, and 0.59‐fold, respectively, and the corresponding mRNA expression in the jejunum were significantly decreased to 0.66‐fold, 0.55‐fold, and 0.64‐fold levels, respectively, relative to their levels in the control group. Conclusions: BBR altered the pharmacokinetics of florfenicol, probably related to its inhibition of CYP3A37, MDR1, and CXR mRNA expression in the jejunum and liver. Abstract : We investigated the effects of berberine on the pharmacokinetics of florfenicol in broilers. The plasma concentrations of florfenicol in broilers with or without BBR pre‐treatment were determined by UHPLC method. In addition, the effects of berberine on CYP3A37, MDR1, and CXR mRNA expression in broilers were determined by real‐time PCR. The results indicated that berberine altered the pharmacokinetics of florfenicol, probably be related to its inhibition of CYP3A37, MDR1, and CXR mRNA expression in the jejunum and liver.